2012
DOI: 10.1016/j.intimp.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Artin M enhances TNF-α production and phagocytosis of Candida albicans mediated by dectin-1 and mannose receptors

Abstract: The activities of dectin-1 and mannose receptors on phagocytosis of Candida albicans and the production of TNF-α by macrophages from mice pretreated for 3 days with extract of Artocarpus intergrifolia seeds (jack extract), Artin M or jacalin were studied. Macrophages from these mice were coincubated with C. albicans CR15 (yeast), in the presence of mannose (50mM) plus mannan (100 μg) or laminarin (1mg). Phagocytosis was significantly enhanced to 52% in macrophages from mice pretreated intraperitoneally for 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Several lectins obtained from vegetal sources have been reported for promoting biological responses such as the recruitment of neutrophils and activation of macrophages with production of TNF-α and IL-12, important for the development of the inflammatory process and modulation of the immune response that culminates with the resolution of infections [23], [24], [25]. The Eutirucallin lectin has immune-stimulator potential, promoting the recruitment of neutrophils in vitro and inducing the production of TNF-α, IL12 and NO by murine macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several lectins obtained from vegetal sources have been reported for promoting biological responses such as the recruitment of neutrophils and activation of macrophages with production of TNF-α and IL-12, important for the development of the inflammatory process and modulation of the immune response that culminates with the resolution of infections [23], [24], [25]. The Eutirucallin lectin has immune-stimulator potential, promoting the recruitment of neutrophils in vitro and inducing the production of TNF-α, IL12 and NO by murine macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Con A in enhancing the ability of mouse peritoneal cells to kill pathogen by increasing the expression of mannose receptors on the cell surface is also reported (Loyola et al, 2002). Artin M and jacalin lectins, isolated from Artocarpus integrifolia (Raval et al, 2004) have been reported to contain C. albicans infection and enhance the survival of infected swiss mice (Custodio et al, 2011) by affecting Th1 and Th17 response, mannose receptor expression, TNF-α production and bacterial killing (Custodio et al, 2011;Loyola et al, 2012). Coltri et al have reported that Artin M can also act against Paracoccidioides brasilensis and conclusively prove that Artin M treated mice had less fungal load in lungs and pulmonary lesions in comparison to untreated mice with increased production of IL-12 in TLR-2 dependent manner (Coltri et al, 2008).…”
Section: Immune Response Mediated By Plant Lectinsmentioning
confidence: 99%
“…Phagocytosis is the main mechanism for fungal elimination (Leopold et al, 2016), and is associated with increased survival of infected animals. Artin M (another mannose-specific lectin, like pCramoll) demonstred that phagocytosis was also the mechanism responsible for Candida albicans elimination, reducing the fungal burden in target organs and increasing animal survival (Loyola et al, 2012). …”
Section: Discussionmentioning
confidence: 99%